Progression and interventional therapy of a coronary pseudoaneurysm: a case report. Issue 1 (15th December 2022) - Gersch, Svante; Baraki, Hassina; Toischer, Karl
Abstract: Background: Coronary pseudoaneurysms (PSAs) occur as a rare complication following drug-eluting stent implantation and have been reported to occur between 1 week and 4 years after implantation. Most of them remain in a stable state, but progression of PSAs increases the risk of rupture and haemorrhagic cardiac tamponade. Case summary: Here, we present a case of a 55-year-old patient, who developed a PSA of the proximal left circumflex artery after stent implantation of the left main artery, left anterior descending artery, and left circumflex artery. Within <1 year, the patient was readmitted to different hospitals due to cardiac decompensation and myocardial infarction. Thereafter, coronary angiography and computed tomography scans were performed, and progression of the PSA could be documented. Interventional therapy was chosen due to the high surgical risk of the patient. Implantation of a covered stent from the left main artery into the left anterior descending artery was chosen to treat the PSA, thereby silencing the chronically occluded left circumflex artery, followed by dilatation with a non-compliant balloon. The patient has remained asymptomatic in a 6-month follow-up. Discussion: Coronary PSA should be controlled with respect to progression, and appropriate therapy can be chosen for treatment.